Nuances of fetal inheritance: A comparative study - Ahmed Alsabawy; Nashwan Sulaiman (الرافدین للحقوق)
The science of inheritance is one of the most important branches of legal studies, serving as a foundational source for personal status laws. It outlines the rules for distributing a deceased person's estate fairly among rightful heirs, without discrimination based on race or gender. Islamic jurisprudence has approved and detailed these inheritance laws for heirs. However, Muslim jurists have differed in their interpretations of certain inheritance cases, especially when issues appear similar in form but differ in legal rulings. This gave rise to what is known as the science of legal differences, which holds significant value alongside other legal disciplines concerning acts of worship and transactions, including inheritance. Among the debated issues is the inheritance of a fetus, where various rulings have emerged across different Islamic schools of thought. The Iraqi legislator, in the Personal Status Law, has referred most matters related to fetal inheritance to the general principles of Islamic law or to the doctrine followed by the deceased prior to the enactment of the law. This approach, however, has resulted in legislative gaps and inconsistencies in addressing various scenarios related to the inheritance of a fetus and similar contested issues.